SLA printing of POSS-containing, bio-based composites with low dielectric constant and shape-memory function. (April 2023) - Hu, Zhendong; Liu, Mengting; Che, Junbo; Kang, Qi; Liu, Ziyi; Qiang, Zhe; Liu, Xueqing; Xia, Yumin; Huang, Shuohan; Zhang, Jianming; Chen, Yuwei
Abstract: Improving sustainability and functionality of resins is important for the development of 3D printing technologies. This work demonstrates a novel bio-based and low dielectric resin containing polyhedral oligomeric silsesquioxane (POSS) for stereolithography (SLA) printing to fabricate sensors and shape memory materials with complex geometry. Epoxidized soybean oil (ESO) and methacrylic acid are used to synthesize a biobased methacrylate resin (MESO) via a ring-opening reaction, followed by incorporation of POSS into polymer matrix. In general, the viscosity of POSS/MESO composite resins is in the range of 0.40–0.58 Pa s, making them viable for SLA printing designs. With the addition of 5 wt% POSS, POSS/MESO composites can exhibit excellent mechanical properties, including tensile strength (18.9 MPa), elongation at break (19.8%), and toughness (399.2 MJ/m3). Furthermore, these materials have a very low dielectric constant of 2.97 at 1 MHz, which is desired for microelectronic applications to overcome signal delay and energy loss. In addition, presence of permanent and reversible networks formed by MESO and POSS endows the POSS/MESO composites with good shape memory property. The application demonstrators include fabrication of flexible interdigital electrode sensors and temperature-responsive sensors. Overall, this work provides great potential opportunities to design the bio-based functional sensor with on-demand control over structures by SLA printing. Graphical abstract: Image 1 Highlights: A novel Biobased SLA printable methacrylate resin was designed and synthesized. POSS was employed to improve mechanical strength, thermal stability, dielectric and shape memory properties. The dielectric constant of 5 wt% POSS/MESO composites was as low as 2.97 (1 MHz). The POSS/MESO composites can be used as flexible sensor to detect the deformation process by the electrical signals.